2020
DOI: 10.1007/s10856-020-06443-0
|View full text |Cite
|
Sign up to set email alerts
|

Filling ability of three variants of the single-cone technique with bioceramic sealer: a micro-computed tomography study

Abstract: The present study evaluated the quality of single-cone root canal fillings with bioceramic (BC) sealer using three different techniques by means of micro-computed tomography (micro-CT). The canals of 30 extracted single-rooted permanent teeth were shaped with R40 Reciproc blue files and filled with the single-cone technique (SCT). BioRoot RCS BC sealer was placed inside the canals with one of the following master cones: R40 cone to working length (RWL, n = 10); R40 cone trimmed 1 mm short of working length (RW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 33 publications
1
22
2
Order By: Relevance
“…Clinically, this finding is relevant, as coronal leakage occurs in a corono-apical fashion. Previous studies have shown an increased number of voids at the coronal aspect for single-cone techniques [33,34]. Hence, an increased sealer penetration at this level, as promoted by activation, may prevent tubular reinfection and limit the reservoir potential of coronal dentine for secondary endodontic infections.…”
Section: Discussionmentioning
confidence: 97%
“…Clinically, this finding is relevant, as coronal leakage occurs in a corono-apical fashion. Previous studies have shown an increased number of voids at the coronal aspect for single-cone techniques [33,34]. Hence, an increased sealer penetration at this level, as promoted by activation, may prevent tubular reinfection and limit the reservoir potential of coronal dentine for secondary endodontic infections.…”
Section: Discussionmentioning
confidence: 97%
“…Different methods to evaluate the porosity and microleakage of the fillings, such as bacterial, glucose, radioactive isotope, or dye penetration tests, have been used with their significant limitations [ 37 ]. Recently, the microcomputed tomography was considered as the optimal, non-destructive method allowing quantify and qualify the high-resolution images in 2D and 3D [ 8 , 12 , 33 ]. Therefore, in our study, the assessment of the porosity of the SC fillings was performed using µCT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the better obturation quality was achieved by students in a postgraduate endodontic program in comparison to undergraduates [ 27 ]. However, it has been claimed that the recently introduced a simplified single cone root canal obturation technique potentially can be less related to the clinical experience of the operator [ 12 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantage of the µCT method is its nondestructiveness, repeatability, and high accuracy [17]. There are few published articles, evaluating the porosity of SC root-canal fillings [14,17,28]. However, there is no data about porosity distribution in the SC fillings, performed by operators with different competencies and clinical experience.…”
Section: Introductionmentioning
confidence: 99%